PENGARUH PENDAPATAN DAN SUKU BUNGA DEPOSITO TERHADAP PERMINTAAN UANG M1 DAN M2 DI INDONESIA - Yenny Ertika; Filia Hanum (Universitas Teuku Umar, 2019)
The study aims to analyse the influence of revenue (which is derived from the gross domestic product data) and 3 month deposit interest rates on the demand for M1 and M2 money in Indonesia using quarterly data from 1992. I-2017. IV. Through the test of symmetry (Wald Statistics test) indicates that there is a shifting allocation of money demand from the demand for money M1 to M2 money demand. The analytical model used is the smallest quadratic method (OLS) and the SURE estimation model to test how much influence the dependent variable affects independent variables. The results of the study found that the use of the SURE model in this study was better and more efficient than using the smallest squared method model equation (OLS) because of the SURE method, evidenced by the standard (SE) and P-value (Prob) Errors of the SURE method are smaller than the standard error (SE) in the OLS method and all P-values of the two equations that are estimated through the SURE model are the magnitude of α < 0.05. So it can be concluded that there is a contemporary correlation between faults or residues of different equations. Furthermore, regression analysis results showed that the income variables had a positive and significant influence on the demand for money for M1 and M2, while 3-month deposit interest rates had negative and significant effects on money demand for M1 and M2.Keywords: Money request, income, 3 months deposit interest rate, OLS, SURE.